We have two responses for you
I assume you are to solve for P. I would use logarithms to solve this problem. I am going to use the natural logarithm (log base e), called ln on my calculator, but you can use the common logarithm (log base 10) if you wish. You should do the calculatios yourself so I'm going to illustrate with different numbers.
Solve for P where
Taking the natural logarithm of both sides I get
I hope this helps,
First isolate the major problem:
(1-P)^75 = 0.95
Remember your rules of exponents: (x^y)^z = x^(yz).
So if z = 1/y, then yz = 1 so you can eliminate the exponent: [(1-P)^75]^(1/75) = 1-P
That means the next step is just to apply the reciprocal of the exponent to both sides:
[ (1-P)^75 ] ^ (1/75) = 0.95 ^ (1/75)
1 - P = 0.95 ^ (1/75)
Solve for P:
P = 1 - 0.95 ^ (1/75)
and turn to your calculator for the rest.
Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences.